2022
DOI: 10.3390/cimb44020050
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of SH003 and Trichosanthes kirilowii Maximowicz in Paclitaxel-Induced Neuropathic Pain in Mice

Abstract: Pacliatxel is a taxol-based chemotherapeutic drug that is widely used to treat cancer. However, it can also induce peripheral neuropathy, which limits its use. Although several drugs are prescribed to attenuate neuropathies, no optimal treatment is available. Thus, in our study, we analyzed whether SH003 and its sub-components could alleviate paclitaxel-induced neuropathic pain. Multiple paclitaxel injections (cumulative dose 8 mg/kg, i.p.) induced cold and mechanical allodynia from day 10 to day 21 after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…However, most of these therapies exhibited moderate efficacy and significant side effects such as somnolence, constipation, tolerance, and dizziness [ 60 ]. In addition, some treatments only improved neuropathy or one of the emotional disorders associated with chemotherapy-induced neuropathic pain [ 61 , 62 , 63 ], but only a few studies evaluated the possible effects of different treatments in the management of PIPN-associated mood disorders [ 13 , 64 , 65 ]. In this line, this study demonstrated that treatment with HRW inhibited neuropathy and avoided the cognitive and emotional deficits associated.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these therapies exhibited moderate efficacy and significant side effects such as somnolence, constipation, tolerance, and dizziness [ 60 ]. In addition, some treatments only improved neuropathy or one of the emotional disorders associated with chemotherapy-induced neuropathic pain [ 61 , 62 , 63 ], but only a few studies evaluated the possible effects of different treatments in the management of PIPN-associated mood disorders [ 13 , 64 , 65 ]. In this line, this study demonstrated that treatment with HRW inhibited neuropathy and avoided the cognitive and emotional deficits associated.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the dose-dependent antinociceptive effect of CucD against paclitaxel-induced cold and mechanical allodynia was demonstrated, along with its underlying mechanism of action. In our previous study, we demonstrated that TK could significantly decrease paclitaxel-induced allodynia and suggested that these effects may be due to CucD ( Lee et al, 2022 ). In this study, CucD was identified in TK by HPLC along with CucB, and their toxicities on non-cancerous and cancerous cells, and RAW 264.7 and Caco-2 cells, respectively, were analyzed.…”
Section: Discussionmentioning
confidence: 95%
“…In our previous study, we demonstrated the antinociceptive effect of TK on paclitaxel-induced allodynia ( Lee et al, 2022 ) and showed that spinal noradrenergic receptors play an important role in the effect of TK. Furthermore, as cucurbitacins are major components of TK, we have suggested that they may play an important role in the antinociceptive effect.…”
Section: Introductionmentioning
confidence: 99%
“… 38 Furthermore, SH003 has been found to alleviate neuropathic pain induced by paclitaxel and docetaxel. 57 , 58 If such co-administration of herbal medicines and chemotherapy has similar effects in humans, patients who would otherwise need to discontinue treatment or reduce dosage due to adverse effects might be able to continue treatment. Given these promising results, continued research and attention are warranted to fully elucidate the benefits and potential of co-administration of herbal formula with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%